2000
DOI: 10.1038/oby.2000.32
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, Obesity, and Blood Pressure: The Effects of Modest Weight Reduction

Abstract: MERTENS, ILSE L., LUC F. VAN GAAL. Overweight, obesity and blood pressure: the effects of modest weight reduction-a review. Obes Res. 2000;8:270 -278.Several large epidemiological studies have shown an association between body mass index and blood pressure in normal weight and overweight patients. Weight gain in adult life especially seems to be an important risk factor for the development of hypertension. Weight loss has been recommended for the obese hypertensive patient and has been shown to be the most eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
150
0
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(185 citation statements)
references
References 59 publications
14
150
0
11
Order By: Relevance
“…Cetilistat (ATL-962), a novel lipase inhibitor P Kopelman et al Treatment with cetilistat also had a beneficial effect on the factors commonly associated with the risk of obesity-related co-morbidities. Modest reductions in bodyweight (5-10%) have been shown to improve glycaemic control, 18 hypertension 6 and cardiovascular disease risk. 19 Approximately 30% of patients in each treatment group achieved a weight loss of at least 5% after 12 weeks, compared to 17% in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetilistat (ATL-962), a novel lipase inhibitor P Kopelman et al Treatment with cetilistat also had a beneficial effect on the factors commonly associated with the risk of obesity-related co-morbidities. Modest reductions in bodyweight (5-10%) have been shown to improve glycaemic control, 18 hypertension 6 and cardiovascular disease risk. 19 Approximately 30% of patients in each treatment group achieved a weight loss of at least 5% after 12 weeks, compared to 17% in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] A sustained weight loss of between 5 and 10% of initial body weight has been associated with clinically meaningful reductions in these obesity-related comorbidities. [5][6][7] Effective pharmacotherapies that can produce sustained weight loss of this magnitude, when accompanied by an acceptable adverse effect profile are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…44 A recent study 45 found an evident association between obesity and a decrease in the expression of D 2 receptors in the brain of obese individuals (BMI Ͼ40 k/m 2 ). Since DA regulates the brain reward circuits producing an agreeable feeling as a response to certain stimuli, 46,47 deficiency in DA action in these patients could perpetuate pathological intake as a means to compensate a decrease in these circuits, the socalled Reward Deficiency Syndrome.…”
Section: Obesity and Hypertensionmentioning
confidence: 99%
“…More important, this study ruled out key variables and potential confounders that could affect blood pressure. Weight loss, loss of adiposity, and increases in activity are known to have positive effects on blood pressure profiles 35, 36, 37, 38, 39. However, the experimental paradigm used in the current study uses obese mice that share similar metabolic profiles in that body mass, total fat content, oxygen consumption, and activity levels remain unchanged with or without increased muscle mass.…”
Section: Discussionmentioning
confidence: 99%